The Influence of Safety Leadership and Working Condition on Safety Behavior: A Systematic Literature Review - Dudija, Nidya; Narendra, Made Diksi (Publisher Cv. Inara, 2024)
This systematic literature review aims to evaluate the influence of safety leadership dan working condition on safety behavior. The methodology involved a comprehensive search and selection of peer-reviewed articles published between 2017 and 2023. This research succeeded in reviewing 14 studies originating from 10 different countries and having topics related to safety leadership, working conditions and safety behavior. The results also indicate that safety leadership and working condition have a significant influence on safety behavior, both directly and indirectly. The review also highlights the critical role of organizational support in mitigating work accident rate. The study concludes that addressing safety behavior through strategic interventions and leadership development to enhance safety leadership and working condition related program can prevent work accident. By recognizing and addressing these issues, it is hoped that management will gain a better and more comprehensive understanding of issues related to safety behavior to give organizational support in order to correctly determine safety programs.